Extractive Institutions, Choking Taxes, and War: On the (Beneficial) Impact of Inequality in Autocracies - Soeren Schwuchow (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We develop a framework for analyzing how the distribution of income-earning ability among citizens affects an autocrat's extractive policies and her intended risk of war. Relying on a general equilibrium model, we show that (i) autocrats can utilize the military for redistribution and (ii) are most powerful for extreme un-/equal distributions. Consequently, ordinary citizens benefit from not-too-low inequality. Our model also implies that disastrous economic policies, characteristic for many kleptocratic autocracies, are not necessarily unintended side effects of rent-seeking but rationally chosen governance. Depending on the level of inequality, autocrats can deter foreign threats by choking the economy. This policy may prevent hostilities but also causes ordinary citizens to favor war since the autocrat would then loose her grip at home. Our results help to explain why some autocrats maintain far-too-great armies, while others suffocate their economies, and yet others were drawn into wars.
Keywords: D74; H56; D74; D31; 330; Inequality; autocracies; corruption; conflict